2018
DOI: 10.1021/jacs.8b04929
|View full text |Cite
|
Sign up to set email alerts
|

Highly Emissive Self-Assembled BODIPY-Platinum Supramolecular Triangles

Abstract: Light-emitting supramolecular coordination complexes (SCCs) have been widely studied for applications in the chemical and biological sciences. Herein, we report the coordination-driven self-assembly of two highly emissive platinum(II) supramolecular triangles (1 and 2) containing BODIPY-based bridging ligands. The metallacycles exhibit favorable anticancer activities against HeLa cells (IC of 6.41 and 2.11 μM). The characteristic ∼570 nm fluorescence of the boron dipyrromethene (BODIPY) moieties in the metalla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
172
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(173 citation statements)
references
References 44 publications
(12 reference statements)
1
172
0
Order By: Relevance
“…Recently, Yu, Huang, and Cook et al . constructed two highly emissive platinum(II) supramolecular triangles 56 and 57 containing BODIPY‐based bridging ligands through the coordination‐driven self‐assembly of a BODIPY ligand 53 with Pt(II) acceptors 54 or 55 in a 1 : 1 ratio in CH 2 Cl 2 /DMA at 60 °C for 24 h (Scheme ) . Confocal laser scanning microscopic (CLSM) investigation confirmed that the NPs containing the metallacycles 56 or 57 were internalized by human cervical cancer cells (HeLa) as witnessed by the observation that the HeLa cells exhibited strong intracellular fluorescence after incubation with the nanoparticles (NPs) containing the metallacycles 56 or 57 for 8 h (Figure ).…”
Section: Functionalized Supramolecular Metallacyclesmentioning
confidence: 95%
“…Recently, Yu, Huang, and Cook et al . constructed two highly emissive platinum(II) supramolecular triangles 56 and 57 containing BODIPY‐based bridging ligands through the coordination‐driven self‐assembly of a BODIPY ligand 53 with Pt(II) acceptors 54 or 55 in a 1 : 1 ratio in CH 2 Cl 2 /DMA at 60 °C for 24 h (Scheme ) . Confocal laser scanning microscopic (CLSM) investigation confirmed that the NPs containing the metallacycles 56 or 57 were internalized by human cervical cancer cells (HeLa) as witnessed by the observation that the HeLa cells exhibited strong intracellular fluorescence after incubation with the nanoparticles (NPs) containing the metallacycles 56 or 57 for 8 h (Figure ).…”
Section: Functionalized Supramolecular Metallacyclesmentioning
confidence: 95%
“…Zhou et al designed supramolecular triangles with vertices comprising novel Pt(II) complexes and edges comprising pyridyl‐functionalized BODIPY . In this design, the BODIPY cores within the triangles were used as PDT PSs, while the presence of Pt(II) complexes were for chemotherapy ( Figure a).…”
Section: Bodipy Nano‐photosensitizers For Pdtmentioning
confidence: 99%
“…The concentration of the formulations was 1.00 × 10 −6 m . All panels reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Bodipy Nano‐photosensitizers For Pdtmentioning
confidence: 99%
“…Moreover, the polypyrrolic photosensitizers have the capability of producing reactive oxygen species via the type two photosensitization process . In addition to that, they are insensitive to solvent, pH, and temperature finding their use in sensing, energy harvesting, water purification, theranostics, and photocatalysis …”
Section: Introductionmentioning
confidence: 99%
“…[9] In addition to that, they are insensitive to solvent, pH, and temperature finding their use in sensing, energy harvesting, water purification, theranostics, and photocatalysis. [10][11][12][13][14][15][16] The major drawback of these polypyrroles is that they are mostly hydrophobic in nature, which restricts their practical applicability. Multiple attempts have been made to improve the solubility of BODIPY and porphyrins through their conjugation/ adsorption on metal or metal oxide nanoparticles, [10,17,18] by preparing self-aggregated nanoparticles, [18] through encapsulation into polymers, etc.…”
Section: Introductionmentioning
confidence: 99%